Analisis Tantangan Pelaksanaan Zakat Sebagai Pengurang Penghasilan Kena Pajak: Optimalisasi Sinergi Zakat dan Pajak di Indonesia - Siti Zubaidah; Roisatun Kasanah; Fitria Idham Chalid; Nurhisna; Anik Sunariyah; Enni Endriyati; Achmad Budi Susetyo (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Law Number 36 of 2008 concerning Income Tax and also Law Number 23 of 2011 concerning Zakat Management which states that zakat can be a deduction from Taxable Income (PKP). However, in terms of implementation, it has not been optimal. The purpose of this study is to analyze the challenges in the implementation of zakat as a deduction from PKP and the optimization of the synergy of zakat and tax in Indonesia. This study uses a qualitative descriptive research approach with the library research method. The results of this study state that the challenges that make it less than optimal include low public understanding, minimal information obtained and not all people pay zakat at BAZ or LAZ due to lack of trust in the institution. Therefore, optimization of the synergy of zakat and tax must be carried out by conducting socialization to both the Directorate General of Taxes and also BAZ or LAZ, increasing the credibility of BAZ and LAZ, and exploring the potential of zakat with a direct tax deduction policy (tax credit). This study provides implications for each stakeholder to synergize in socializing zakat as a deduction from PKP.